The effects of frequency on fatigue threshold and crack propagation rate in modified and unmodified polyvinyl chloride - Samat, Noorasikin; Burford, Robert; Whittle, Alan; Hoffman, Mark (Wiley, 2009)

(untitled)
The cyclic fatigue crack behavior of polyvinyl chloride (PVC), with (PVC-M) and without (PVC-U) chlorinated polyethylene (CPE) impact modifier, was studied. The effect of impact modifier upon fatigue crack growth rate and threshold was evaluated at frequencies of 1, 7, and 20 Hz. It was shown that the addition of CPE lowered the threshold stress intensity factor amplitude for crack growth (ΔKth) of PVC-M compared to that of PVC-U at lower frequencies, and that the effect became more pronounced at lower frequency. At lower stress intensity factor amplitudes (below ΔK = 1 MPa·m1/2), there was a slight difference between the crack growth rates of U- and M-PVC. The crack advance mechanism is investigated by microscopic observation of the crack tip process zone. Although the zone is relatively large in PVC-M, associated with higher toughness, it did not improve the fatigue crack growth resistance significantly. Fracture surface observations reveal a higher density of fibrils on the fatigued surface of PVC-M with the density, relative to that observed in PVC-U, reducing with frequency. It is therefore hypothesized that accelerated fibril failure is a mechanism of fatigue.